2020
DOI: 10.1038/s41467-020-20097-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of exposure to SARS-CoV-2 in cats and dogs from households in Italy

Abstract: SARS-CoV-2 emerged from animals and is now easily transmitted between people. Sporadic detection of natural cases in animals alongside successful experimental infections of pets, such as cats, ferrets and dogs, raises questions about the susceptibility of animals under natural conditions of pet ownership. Here, we report a large-scale study to assess SARS-CoV-2 infection in 919 companion animals living in northern Italy, sampled at a time of frequent human infection. No animals tested PCR positive. However, 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
409
7
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(509 citation statements)
references
References 22 publications
56
409
7
9
Order By: Relevance
“…Other epidemiological studies have been conducted that included samples collected from animals presenting for routine veterinary visits, where there was no known exposure to people infected with SARS-CoV-2. A study of 919 companion animals in Northern Italy that were sampled at a time of frequent human infection reported that 3.3% of dogs and 5.8% of cats displayed titres of neutralising antibodies [70]. In this study, 69 samples for serology originated from dogs (47) and cats (22) from a known COVID-19 affected household and 12.8% (6/47) of these dogs and 4.5% (1/22) of these cats tested positive for SARS-CoV-2-neutralizing antibodies; in addition, the seroprevalence found in dogs from a known COVID-19 positive household was significantly higher than dogs from COVID-19 negative households (1.5%; 2/133) [70].…”
Section: Prevalence Of Sars-cov-2 Infection In Domestic Animalsmentioning
confidence: 99%
“…Other epidemiological studies have been conducted that included samples collected from animals presenting for routine veterinary visits, where there was no known exposure to people infected with SARS-CoV-2. A study of 919 companion animals in Northern Italy that were sampled at a time of frequent human infection reported that 3.3% of dogs and 5.8% of cats displayed titres of neutralising antibodies [70]. In this study, 69 samples for serology originated from dogs (47) and cats (22) from a known COVID-19 affected household and 12.8% (6/47) of these dogs and 4.5% (1/22) of these cats tested positive for SARS-CoV-2-neutralizing antibodies; in addition, the seroprevalence found in dogs from a known COVID-19 positive household was significantly higher than dogs from COVID-19 negative households (1.5%; 2/133) [70].…”
Section: Prevalence Of Sars-cov-2 Infection In Domestic Animalsmentioning
confidence: 99%
“…In a large-scale study assessing SARS-CoV-2 infection in 919 companion animals living in northern Italy, sampled at a time of frequent human infection, none of these pets tested PCR positive. However, 3.3% of dogs and 5.8% of cats had measurable SARS-CoV-2 neutralizing antibody titres; dogs from COVID-19 positive households were significantly more likely to test positive than those from COVID-19 negative households ( 13 ). Higher seroprevalence rates for SARS-CoV-2, ranging from 21 to 53% depending of the test used, were observed in domestic carnivores from COVID-19 positive household in two French regions ( 14 ).…”
Section: Can Dogs and Cats Be Infected By Sars-cov-2?mentioning
confidence: 99%
“…Despite increased understanding from experimental research on felids, cats are not standard experimental animals and are difficult to handle in biosafety 3 settings [174]. Additional field investigations could circumvent these logistical challenges by monitoring environmental contamination (e.g., litter box, food, water bowls) or transmission efficiency between owners and domestic cats [174,175].…”
Section: Felidsmentioning
confidence: 99%
“…On 28 February 2020, in Hong Kong, the first domestic dog that tested positive for SARS-CoV-2 was reported in a Pomeranian dog belonging to an owner that was previously tested positive for SARS-CoV-2 [235]. Subsequent asymptomatic dog infections in Hong Kong were reported; all sharing living environment with at least one SARS-CoV-2-positive owner [175,236,237]. During the same period, in the Netherlands, one pet dog was reported positive for SARS-CoV-2 and its owner had previously been hospitalized for SARS-CoV-2 [238].…”
Section: Canidsmentioning
confidence: 99%